Análisis de algunas variables que influyen en la intención de promocionarse en pantallas led - Calle, Marcelo; Sarmiento Moscoso, David Ariel (UDA AKADEM, 2025)
a publicidad en pantallas LED ha emergido como una opción destacada en el marketing, permitiendo a las empresas llegar dinámicamente a sus audiencias. Este estudio investigó las variables que influyen en la adopción de estas pantallas por parte de las pequeñas y medianas empresas (PYMES) en Cuenca para sus estrategias publicitarias. Se examinó la percepción de costos, la utilidad del servicio y las expectativas de efectividad, evaluando su impacto en la intención de compra. Con un enfoque cuantitativo, se encuestó a 352 PYMES y se emplearon técnicas estadísticas como correlaciones y regresiones lineales para analizar los datos. Los resultados destacaron que la percepción de costos, la utilidad percibida y las expectativas de efectividad influyen positivamente en la intención de compra. En las conclusiones, se enfatizó la importancia de estudiar estas variables para desarrollar estrategias efectivas que fomenten la adopción de tecnologías LED entre las PYMES de Cuenca. Palabras clave: Expectativas de efectividad, percepción de costos, percepción de efectividad, pantallas LED, publicidad. ABSTRACT Advertising strategies on LED screens have become a prominent option in the marketing environment, offering companies a dynamic and attractive way to reach their audiences. This study seeks to analyze the key variables that influence the decision of small and medium-sized businesses (SMEs) in the city of Cuenca to adopt LED screens in their advertising strategies. The variables studied were the perception of costs, the perception of the service’s usefulness, expectations of effectiveness, and how these impact purchase intention as a dependent variable. This study used a quantitative approach based on validated surveys of a sample of 352 SMEs in Cuenca. The collected data were analyzed using statistical techniques, including correlations and linear regressions. The results show that the variable’s perception of costs, perception of usefulness, and expectations of effectiveness directly and positively influence purchase intention. The conclusions indicate that within the strategies of companies marketing this type of technology, it is essential to dedicate time, space, and resources to the study of these variables to generate strategies that allow them to increase the purchase intention of LED technologies in small and medium-sized companies in the city of Cuenca. Keywords: Expectations of effectiveness, perception of costs, perception of effectiveness, LED screens, advertising